As diferentes perspectivas da pediatria a partir das vivências de uma acadêmica de medicina: uma narrativa reflexiva - Nogueira, Marina Mourad (Universidade Federal de São Carlos, 2024)
The word “pediatrics” is of Greek origin, formed by the combination of the terms paidos, which means “child” and iatreia, which means “healing process”, and is used to name the medical specialty dedicated to child care, from birth to adolescence. Since the end of the 19th century, teaching Pediatrics gained prominence in Brazilian medical training, remaining until today as one of the great areas of learning. The medical course at UFSCar includes in its pedagogical project the broad area of ​​child health and of the adolescent, to be studied during the 6 years of graduation. Therefore, The objective of this work is to demonstrate the impact of different experiences on pediatrics throughout a degree in medicine and demonstrate the importance of this specialty in medical and humanitarian training.
The different perspectives of pediatrics from the experiences of a medical student: a reflective narrative
Keywords: Pediatria; Formação médica; Narrativa reflexiva; Educação médica; Pediatrics; Medical training; Reflective narrative; Medical education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM